If the factors are a and b then we can create the equation as :
![(x-a)(x-b)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/ezn15srv368j5hwnzv4j5h4uus8tz12reo.png)
Here we are given the solutions as 1 and -1.
Let us plug them in the above equation and try to make an equation using it.
let a=1 and b=-1
So we have,
![(x-1)(x-(-1))=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/v6iq125b88n5cxb5g11v97srtg73n25eoc.png)
Simplifying,
![(x-1)(x+1)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/j5zljukmjm0ibfp2ouxwkwuxy9zryv2hym.png)
Answer:
The equation with solutions 1 and -1 is:
![(x-1)(x+1)=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/j5zljukmjm0ibfp2ouxwkwuxy9zryv2hym.png)